1994
DOI: 10.1111/1467-9566.ep11347023
|View full text |Cite
|
Sign up to set email alerts
|

The methodology of Focus Groups: the importance of interaction between research participants

Abstract: What are focus groups? How are tbey distinct from ordinary group discussions and wbat use are tbey anyway? Tbis article introduces focus group metbodology, explores ways of conducting sucb groups and examines wbat tbis tecbnique of data collection can offer researcbers in general and medical sociologists in particular. It concentrates on tbe one feature wbicb inevitably distinguisbes focus groups from one-to-one interviews or questionnaires -namely the interaction between research participants -and argues for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
2,089
0
100

Year Published

1998
1998
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 2,756 publications
(2,282 citation statements)
references
References 28 publications
8
2,089
0
100
Order By: Relevance
“…Menarche and menstruation constitute a private realm, difficult to access with conventional scientific methods, and hence a qualitative research approach was believed to be more appropriate for this sensitive topic. Focus groups were chosen over dyadic interviews, Women's Menarche Stories 10 because research has shown that in focus groups, people may be more, rather than less, likely to self-disclose or share personal experiences (Morgan & Krueger, 1993;Carey, 1994;Kitzinger, 1994a). Also, feminist critiques of one-to-one interviews (Oakley, 1981) anticipate the more recent finding that people can feel relatively empowered and supported in a group situation, surrounded by peers or friends (e.g., Fuller, Edwards, Vorakitphokatorn, & Sremsri, 1993).…”
Section: Methodsmentioning
confidence: 99%
“…Menarche and menstruation constitute a private realm, difficult to access with conventional scientific methods, and hence a qualitative research approach was believed to be more appropriate for this sensitive topic. Focus groups were chosen over dyadic interviews, Women's Menarche Stories 10 because research has shown that in focus groups, people may be more, rather than less, likely to self-disclose or share personal experiences (Morgan & Krueger, 1993;Carey, 1994;Kitzinger, 1994a). Also, feminist critiques of one-to-one interviews (Oakley, 1981) anticipate the more recent finding that people can feel relatively empowered and supported in a group situation, surrounded by peers or friends (e.g., Fuller, Edwards, Vorakitphokatorn, & Sremsri, 1993).…”
Section: Methodsmentioning
confidence: 99%
“…Practically, this snowball sampling afforded the recruitment of homebound participants who otherwise would have been difficult to recruit. Moreover, these relationships promoted naturalistic interactions between the two dyads who could relate to and share observations about each other’s experiences (Kitzinger, 1994). Conducting two single-session, extended-duration focus groups also had both advantages and disadvantages.…”
Section: Limitationsmentioning
confidence: 99%
“…sexuality, although focus groups may capture the delicacies of this sensitivity, and break the ice to allow shyer individual's to participate (Kitzinger, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…There has been much support in the literature for the view that focus groups are an appropriate method of choice for health research into sensitive issues, and for investigating people's experiences of illness and in using the health services (Kitzinger, 1994(Kitzinger, , 2000Green & Thorogood, 2004). While group interviewing may be conducted using a variety of styles, our emphasis here is on analysing interviews where adolescents previously known to one another are brought together for the purposes of generating data about a topic -in this case sexual health -in an informal atmosphere.…”
Section: Introductionmentioning
confidence: 99%